Emerging low-power semiconductor devices - Tayal, Shubham (Boca Raton : CRC Press, 2023)
"This book will give insight into the emerging semiconductor devices from their applications in electronic circuits. This book discusses the challenges in the field of engineering and applications of advanced low-power devices"--
Role of TFET devices and their performance analysis for wireless communications / B. Lokesh, B. Lakshmi.
OCLC-licensed vendor bibliographic record.
Keywords: Low voltage integrated circuits; Semiconductors; COMPUTERS / Computer Engineering; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / Circuits / General